Weathering change: climate change vulnerability and women in cocoa farming - Friedman, R (2015)
Climate change is increasingly recognized as a hurdle to achieving development goals in developing countries and emerging economies. While mitigation is still a focus of many climate change activities, adaptation strategies are recognized as essential to respond to the current and projected impacts of climate change. The concept of vulnerability is often used to identify what adaptation measures must specifically address, and is discussed in terms of three components: exposure to shocks or long-term stress; sensitivity of a system to the event; and capacity to adapt. Women are considered a vulnerable demographic, because of their reduced access to land, financial and productive resources, and information. This dissertation integrates a vulnerability framework with gender considerations as a means to explore many of the factors influencing climate change vulnerability among women in a case study of cocoa farming in the Central Region of Ghana. The research is based on semi-structured interviews with female members of three communities, representing a cross-section of the different associations with land and farm decision-making, ranging from primary operators of cocoa farms to producers of food crops on a spouse’s land for subsistence and local markets. The interviews highlighted the importance of income sources and diversification, access to information, and perceptions of empowerment and agency as contributors to vulnerability to projected climate change impacts. Women without direct access to cocoa generally had fewer assets at their disposal and shorter planning horizons that might lead to greater vulnerability. Despite these differences, most of the women demonstrated a positive outlook and future orientation that is often taken as a sign of adaptive capacity. This research demonstrated the need for more nuanced assessment of vulnerability among women, but also for rethinking the depiction of women as disempowered actors and the types of policies crafted to support climate change adaptation and development.